Tumor-infiltrating CCR2+ inflammatory monocytes counteract specific immunotherapy - Bartneck, Joschka; Hartmann, Ann-Kathrin; Stein, Lara; Arnold-Schild, Danielle; Klein, Matthias; Stassen, Michael; Marini, Federico; Pielenhofer, Jonas; Meiser, Sophie Luise; Langguth, Peter; Mack, Matthias; Muth, Sabine; et al. (Frontiers in Immunology, 2023)
Tumor development and progression is shaped by the tumor microenvironment (TME), a heterogeneous assembly of infiltrating and resident host cells, their secreted mediators and intercellular matrix. In this context, tumors are infiltrated by various immune cells with either pro-tumoral or anti-tumoral functions. Recently, we published our non-invasive immunization platform DIVA suitable as a therapeutic vaccination method, further optimized by repeated application (DIVA 2 ). In our present work, we revealed the therapeutic effect of DIVA 2 in an MC38 tumor model and specifically focused on the mechanisms induced in the TME after immunization. DIVA 2 resulted in transient tumor control followed by an immune evasion phase within three weeks after the initial tumor inoculation. High-dimensional flow cytometry analysis and single-cell mRNA-sequencing of tumor-infiltrating leukocytes revealed cytotoxic CD8 + T cells as key players in the immune control phase. In the immune evasion phase, inflammatory CCR2 + PDL-1 + monocytes with immunosuppressive properties were recruited into the tumor leading to suppression of DIVA 2 -induced tumor-reactive T cells. Depletion of CCR2 + cells with specific antibodies resulted in prolonged survival revealing CCR2 + monocytes as important for tumor immune escape in the TME. In summary, the present work provides a platform for generating a strong antigen-specific primary and memory T cell immune response using the optimized transcutaneous immunization method DIVA 2 . This enables protection against tumors by therapeutic immune control of solid tumors and highlights the immunosuppressive influence of tumor infiltrating CCR2 + monocytes that need to be inactivated in addition for successful cancer immunotherapy.